Autologous cellular vaccine overcomes cancer immunoediting in a mouse model of myeloma. Issue 1 (15th June 2015) - Mazzocco, Marta; Martini, Matteo; Rosato, Antonio; Stefani, Elisabetta; Matucci, Andrea; Dalla Santa, Silvia; De Sanctis, Francesco; Ugel, Stefano; Sandri, Sara; Ferrarini, Giovanna; Cestari, Tiziana; Ferrari, Sergio; et al.
Summary In the Sp6 mouse plasmacytoma model, a whole‐cell vaccination with Sp6 cells expressing de novo B7‐1 (Sp6/B7) induced anatomically localized and cytotoxic T cell (CTL) ‐mediated protection against wild‐type (WT) Sp6. Both WT Sp6 and Sp6/B7 showed down‐regulated expression of MHC H‐2 Ld. Increase of H‐2 Ld expression by cDNA transfection (Sp6/B7/Ld) raised tumour immune protection and shifted most CTL responses towards H‐2 Ld‐restricted antigenic epitopes. The tumour‐protective responses were not specific for the H‐2 Ld‐restricted immunodominant AH1 epitope of the gp70 common mouse tumour antigen, although WT Sp6 and transfectants were able to present it to specific T cells in vitro. Gp70 transcripts, absent in secondary lymphoid organs of naive mice, were detected in immunized mice as well as in splenocytes from naive mice incubated in vitro with supernatants of CTL‐lysed Sp6 cell cultures, containing damage‐associated molecular patterns (DAMPs). It has been shown that Toll‐like receptor triggering induces gp70 expression. Damage‐associated molecular patterns are released by CTL‐mediated killing of Sp6/B7‐Sp6/B7/Ld cells migrated to draining lymph nodes during immunization and may activate gp70 expression and presentation in most resident antigen‐presenting cells. The same could also apply for Mus musculus endogenous ecotropic murine leukaemia virus 1 particles present in Sp6‐cytosol, discharged by dying cells and superinfecting antigen‐presenting cells. The outcome of such a massive gp70 cross‐presentation would probably be tolerogenic for the high‐affinity AH1‐gp70‐specific CTL clones. In this scenario, autologous whole‐tumour‐cell vaccines rescue tumour‐specific immunoprotection by amplification of subdominant tumour antigen responses when those against the immune dominant antigens are lost.